The Holographic Human: Review of Dominic Pettman, Human Error: Species-Being and Media Machines - Grebowicz, Margret (Humanimalia, 2013)
Dominic Pettman. Human Error: Species-Being and Media Machines. Minneapolis: University of Minnesota Press, 2011. 360 pp.